Organic Acids as Alternatives for Antibiotic Growth Promoters Alter the Intestinal Structure and Microbiota and Improve the Growth Performance in Broilers - Dai, Dong; Qiu, Kai; Zhang, Hai-jun; Wu, Shu-geng; Han, Yan-ming; Wu, Yuan-yuan; Qi, Guang-hai; Wang, Jing (Frontiers in Microbiology, 2021)
The present study aimed to investigate the effects of organic acids (OA) as alternatives for antibiotic growth promoters (AGP) on growth performance, intestinal structure, as well as intestinal microbial composition and short-chain fatty acids (SCFAs) profiles in broilers. A total of 336 newly hatched male Arbor Acre broiler chicks were randomly allocated into 3 dietary treatments including the basal diet (negative control, NC), the basal diet supplied with flavomycin, and the basal diet supplied with OA feed additives. Each treatment had 8 replicates with 14 birds each. The results showed that AGP and OA promoted growth during d 22 to 42 compared with the NC group (P < 0.05). OA significantly increased the jejunal goblet cells density and ileal villus height on d 42 compared with the NC group (P < 0.05). Meanwhile, OA up-regulated the mRNA expression of jejunal barrier genes (Claudin-3 and ZO-1) relative to the NC group (P < 0.05). Significant changes of microbiota induced by the OA were also found on d 42 (P < 0.05). Several SCFAs-producing bacteria like Ruminococcaceae, Christensenellaceae and Peptococcaceae affiliated to the order Clostridiales were identified as biomarkers of the OA group. Higher concentrations of SCFAs including formic acid and butyric acid were observed in the cecum of OA group (P < 0.05). Simultaneously, the abundance of family Ruminococcaceae was showed highly positive correlations with the body weight and mRNA level of ZO-1 on d 42 (P < 0.05). However, the higher mRNA expression of Claudin-2, lower goblet cells density of jejunum, and decreased Firmicutes to Bacteroidetes ratio were observed in the AGP group, suggesting that AGP supplementation might have a negative impact on intestinal immune and microbiota homeostasis. In conclusion, supplemental the OA improved growth performance, intestinal morphology and barrier function in broilers, which might be attributed to the changes of intestinal microbiota, particularly the enrichment of SCFAs-producing bacteria, providing a more homeostatic and healthy intestinal microecology.